Compatibility and trade-off between performance: an alternative view - Mapes, John (Cranfield University, 1995)
An issue on which opinions still differ concerns the presence or absence of trade-offs between different types of manufacturing performance. In an attempt to provide some empirical evidence to resolve this argument, a recent conference paper examined the relationships between different types of performance for a sample of plants in the metal/mechanical industry. The authors concluded that trade-offs between several performance types still exist. This paper provides a different interpretation of the data presented, using statistical analysis to demonstrate that the evidence for trade-offs is not significant. However, there is evidence that some types of performance are mutually supportive. The results obtained are compared with the results predicted by each of the available trade-off models and some empirical support for the sand cone model is obtained.